Finance and Development, March 1982. (Finance and Development; Finance and Development ;, 1982)
This paper highlights that important changes have been made in the World Bank's management systems since Mr. A. W. Clausen became President in July 1981. The changes reflect Mr. Clausen's belief that there needs to be a more collegial approach to decision making and greater delegation of authority. The aim is that the World Bank should become more efficient and its activities should be more responsive to its clients' needs. A Managing Committee was also established to take decisions on all key issues facing the World Bank.